2019
DOI: 10.1002/2050-7038.12099
|View full text |Cite
|
Sign up to set email alerts
|

Annual energy loss reduction of distribution network through reconfiguration and renewable energy sources

Abstract: Summary Renewable energy sources are becoming popular day by day for distributed generation as technology is becoming cheaper and modular. Power loss reduction is a powerful incentive for a distribution system operator to promote distributed generation. This paper presents a method to minimize annual energy losses through the integration of nondispatchable renewable distributed generation (DG) units and network reconfiguration under varying load demand condition. The optimal location and DG power level are cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 82 publications
0
16
0
1
Order By: Relevance
“…In India, nearly 65% of the total demand is supplied by fuel‐based power plants. The increases in air pollution, global warming gases, and cost of fuel‐based power plants have increased the concern over the development of renewable sources 1–5 . During the last few decades, there has been an enormous interest in the development of renewable energy source‐based power plants.…”
Section: Introductionmentioning
confidence: 99%
“…In India, nearly 65% of the total demand is supplied by fuel‐based power plants. The increases in air pollution, global warming gases, and cost of fuel‐based power plants have increased the concern over the development of renewable sources 1–5 . During the last few decades, there has been an enormous interest in the development of renewable energy source‐based power plants.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in distribution networks, reconfiguration can improve network power quality. The effect of harmonic loads on the network reconfiguration problem has been investigated in [7,23,24] concerning total losses, including fundamental and harmonic losses. In [7], three methods have been compared in terms of speed and convergence including discrete Particle Swarm Optimization (DPSO), Imperialist Competitive Algorithm (ICA) and Shuffled Frog Leaping Algorithm (SFLA).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is also an easier and applicable scheme due to the existence of tie switches (TSs) (normally opened) and sectionalizing switches (SSs) (normally closed) in DNs. DN reconfiguration (DNR) is a low‐cost efficient tool provided for the network operator to improve operational characteristics of the network by changing the network configuration 5 . The power quality (PQ) factors of a special group of costumers could be improved by just changing the state of TSs and SSs.…”
Section: Introductionmentioning
confidence: 99%